Scanning electron microscopy of floral initiation and developmental stages in Sweet cherry (Prunus avium L.) under water deficits (Bangladesh Journal of Botany, 2008)
The influence of different irrigation conditions on flower bud development of the sweet cherry cv. â0900 Ziraat' was studied using scanning electron microscopy. Flower bud development was compared in three irrigation treatments. Control trees (I100) were irrigated at approximately 100% ET. Stress treatments received 50% (I50) and 20% (I20) of the water applied to the control. The rate of flower bud initiation at the stage of differentiation of sepal, petal, stamen and pistil primordia was considerably slower at I20 as compared to the more irrigated treatments. Also, when water was not provided in the next year, flower bud initiation and differentiation was delayed. These results suggested that the lower the irrigation, the slower the progression of flower differentiation. Â  Key words: Floral initiation, Bud differentiation, Irrigation, Prunus avium, Sweet cherry doi:10.3329/bjb.v37i1.1558 Bangladesh J. Bot. 37(1): 15-19, 2008 (June)